Unveiling Paradoxes: HDI's Limited Impact on Labor and Economic Growth in Indonesia (2010-2021) - Anitha Ahmad, Risky; Alwahidin, Alwahidin (International Journal of Transdisciplinary Knowledge, 2023)
Unveiling Paradoxes: HDI's Limited Impact on Labor and Economic Growth in Indonesia (2010-2021)